Znaczenie wybranych adipokin w łuszczycy - Anna Baran; Iwona Flisiak; Bożena Chodynicka (Termedia Publishing House, 2011)
Psoriasis is a chronic and recurrent skin disease, affecting 1.5-3% of thepopulation. It is characterized by abnormal epidermal proliferation,immunological disturbances with predominance of Th1 response andcomplex pathogenesis. There are correlations between psoriasis andobesity, cardiovascular diseases, diabetes and metabolic syndrome.Adipokines, bioactive substances secreted by adipose tissue, exerta variety of metabolic activities and are associated with many diseases.In the article the possible role of adipokines in psoriasis is evaluated.